Proceedings. Technology of Object-Oriented Languages. TOOLS 26 (Cat. No.98EX176)
DOI: 10.1109/tools.1998.711000
|View full text |Cite
|
Sign up to set email alerts
|

Building an OMT-editor using design patterns: an experience report

Abstract: This paper discusses the development and implementation of a customizable editor for OMT UML style object-models and behavior-models. A number of well known design patterns are used to obtain a exible architecture that allows to build tool support for our software engineering research requiring variants or add-ons to the basic editors. We report on the di culties we encountered in applying the Model-View-Control, Observer, Visitor, Iterator, Bridge, Facade and Chain of Responsibility patterns and we evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Wydaeghe et al [27] studied the use of six design patterns to build an OMT editor. They discussed the impact of their motifs on reusability, modularity, flexibility, and understandability.…”
Section: Related Workmentioning
confidence: 99%
“…Wydaeghe et al [27] studied the use of six design patterns to build an OMT editor. They discussed the impact of their motifs on reusability, modularity, flexibility, and understandability.…”
Section: Related Workmentioning
confidence: 99%
“…The Secure Geospatial Visualization and Collaboration System has been designed and implemented. Software engineering, object-oriented system design, visualization, web security, and Java technologies as well as the World Wide Web are used in the implementation [10,15,[17][18][19][20]. During system development, the Java 2 Enterprise Edition (J2EE) was chosen as the development platform of this web application.…”
Section: Resultsmentioning
confidence: 99%
“…It brings into software well-developed ideas that are "plug-andplay." Object-oriented technique and design patterns are software engineering technologies that have been used to develop real-world applications for years [14][15][16]. Therefore, using object-oriented system design methodology to build linkages between visualization technology and the WWW has come to fruition.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Prechelt et al [1] reported that design patterns can positively affect maintenance aspects. On the other hand, other studies [7][8][9][10] reported negative impact of design pattern on software quality. Therefore, the question about design patterns impact on software quality is still open due to such inconclusiveness.…”
Section: Introductionmentioning
confidence: 93%